PENGARUH PEMBERIAN INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMP SE-KECAMATAN BUAY MADANG KABUPATEN OKU TIMUR - Sumariyak, Asep; Karwono, Karwono; Muhfahroyin, Muhfahroyin (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2021)
The teacher is one of the determinants of the high and low quality of the results of education, so every effort to improve the quality of education needs to pay great attention to improving teacher performance. To achieve good teacher performance can be achieved through the provision of sufficient incentives and high work motivation from the teacher himself.From the analysis it can be concluded that the results of the study indicate that there is an effect of giving incentives to teacher performance. This proves that giving incentives has a major influence on teacher performance. The results showed that there was an effect of work motivation on teacher performance. This proves that work motivation has a big influence on teacher performance. The results of the study showed that there was an effect of giving incentives and work motivation together on teacher performance. This proves that giving incentives and work motivation has a big influence on teacher performance